Critical Exegesis on the Application of Blockchain in Information Security Across Various Sectors - rodriguez leon, Diego Jair (2025)
Nowadays, the protection of information has become an indispensable and omnipresent need. In this context, blockchain technology has emerged as a disruptive solution, generating a significant impact thanks to its decentralized structure and its ability to provide an immutable and transparent record of transactions. This article aims to analyze how blockchain has been successfully implemented to protect sensitive data, ranging from financial applications to medical records management, through a systematic review of information collected between the years 2018 and 2024. The study offers a comprehensive and updated vision of how this technology is transforming information security, highlighting its growing relevance in a digital environment that is increasingly vulnerable to ciber threats.